Infectious Diseases in an Age of Change: The Impact of Human Ecology and Behavior on Disease Transmission - Bernard Roizman (The National Academies Press, 1995)
Twenty-first century progress against infectious diseases is threatened by urbanization, population growth, war refugees, changing sexual standards, and a host of other factors that open doors to the transmission of deadly pathogens. Infectious Diseases in an Age of Change reports on major infectious diseases that are on the rise today because of changing conditions and identifies urgently needed public health measures. This volume looks at the range of factors that shape the epidemiology of infectious diseases—from government policies to economic trends to family practices. Describing clinical characteristics, transmission, and other aspects, the book addresses major infectious threats—sexually transmitted diseases, Lyme disease, human cytomegalovirus, diarrheal diseases, dengue fever, hepatitis viruses, HIV, and malaria. The authors also look at the rising threat of drug-resistant strains of tuberculosis, rapid exhaustion of the weapons to fight bacterial infections, and prospects for vaccinations and eradication of pathogens. Infectious Diseases in an Age of Change will be important to public health policymakers, administrators, and providers as well as epidemiologists and researchers.
Keywords: Health and Medicine

(NAS Colloquium) Carbon Dioxide and Climate Change (The National Academies Press, 1997)
Keywords: Environment and Environmental Studies; Earth Sciences

Convergence II: The Art Collection of the National Academy of Sciences - National Academy of Sciences (The National Academies Press, 2021)
Science relies on the rational. Art celebrates the intuitive. Together they inform one another. The second volume catalog of the art collection of the National Academy of Sciences illustrates by example how Cultural Programs of the National Academy of Sciences' art exhibits and collection provide a platform for thinking about the impact of science on our society. Through a cultural and personal lens, the topics found in the collection range from diversity and equity to climate change and collaboration. This catalog contains beautiful reproductions of more than 30 original artworks from the National Academy of Sciences collection, including such artists as Tim Rollins and K.O.S., Mike and Doug Starn, Tavares Strachen, Neri Oxman, Camille Seaman, Diane Burko, Renée Stout, Alfredo Arreguín, Jeffrey Kent, David Maisel, and many more. Essays from leading scholars and curators are included that illuminate the work.
Keywords: Explore Science

Report of the Treasurer: For the Year Ended December 31, 2022 - National Academy of Sciences (The National Academies Press, 2023)
Keywords: Policy for Science and Technology

Self-Organized Complexity in the Physical, Biological, and Social Sciences (The National Academies Press, 2002)
Keywords: Biology and Life Sciences; Math, Chemistry, and Physics

Cybersecurity Dilemmas: Technology, Policy, and Incentives: Summary of Discussions at the 2014 Raymond and Beverly Sackler U.S.-U.K. Scientific Forum - National Academy of Sciences (The National Academies Press, 2015)
Individuals, businesses, governments, and society at large have tied their future to information technologies, and activities carried out in cyberspace have become integral to daily life. Yet these activities - many of them drivers of economic development - are under constant attack from vandals, criminals, terrorists, hostile states, and other malevolent actors. In addition, a variety of legitimate actors, including businesses and governments, have an interest in collecting, analyzing, and storing information from and about individuals and organizations, potentially creating security and privacy risks. Cybersecurity is made extremely difficult by the incredible complexity and scale of cyberspace. The challenges to achieving cybersecurity constantly change as technologies advance, new applications of information technologies emerge, and societal norms evolve. In our interconnected world, cyberspace is a key topic that transcends borders and should influence (as well as be influenced by) international relations. As such, both national and international laws will need careful evaluation to help ensure the conviction of cybercriminals, support companies that work internationally, and protect national security. On December 8 and 9, 2014, the Raymond and Beverly Sackler U.S.-U.K. Scientific Forum "Cybersecurity Dilemmas: Technology, Policy, and Incentives" examined a broad range of topics including cybersecurity and international relations, privacy, rational cybersecurity, and accelerating progress in cybersecurity. This report summarizes the presentations and discussions from this forum.
Keywords: Computers and Information Technology

Toward a New Era of Data Sharing: Summary of the US-UK Scientific Forum on Researcher Access to Data - National Academy of Sciences (The National Academies Press, 2024)
Data are at the forefront of efforts to solve many of today's greatest problems, including climate change, misinformation and disinformation, the threat of future global pandemics, and the quest by people everywhere to lead better lives. But if researchers are going to use data to contribute to the solutions of problems, data need to be available for them to use. Over time, data have become increasingly voluminous, complex, and heterogeneous. Massive volumes of data are being generated by new devices and methods, and many of these data are not easy to analyze, interpret, or share. Groups that generate data may be reluctant to share them for a variety of professional, personal, financial, regulatory, and statutory reasons.These issues were addressed during the US-UK Scientific Forum on Researcher Access to Data held in Washington, DC, on September 12–13, 2023. Organized by the National Academy of Sciences and the Royal Society, the forum examined the constellation of issues surrounding researchers' access to data, best practices and lessons learned from exemplary research disciplines, and new ideas and techniques that could drive research forward. This publication summarizes the presentations and discussions of the forum.
Keywords: Policy for Science and Technology

The Frontiers of Machine Learning: 2017 Raymond and Beverly Sackler U.S.-U.K. Scientific Forum - National Academy of Sciences (The National Academies Press, 2018)
The field of machine learning continues to advance at a rapid pace owing to increased computing power, better algorithms and tools, and greater availability of data. Machine learning is now being used in a range of applications, including transportation and developing automated vehicles, healthcare and understanding the genetic basis of disease, and criminal justice and predicting recidivism. As the technology advances, it promises additional applications that can contribute to individual and societal well-being. The Raymond and Beverly Sackler U.S.-U.K. Scientific Forum “The Frontiers  of Machine Learning” took place on January 31 and February 1, 2017, at the Washington, D.C., headquarters of the National Academies of Sciences, Engineering, and Medicine. Participants included industry leaders, machine learning researchers, and experts in privacy and the law, and this report summarizes their high-level interdisciplinary discussions.
Keywords: Engineering and Technology

India-United States Cooperation on Science and Technology for Countering Terrorism: Summary of a Workshop - National Academy of Sciences (The National Academies Press, 2014)
India and the United States are the world's two largest democracies with distinguished scientific traditions and experts in a wide range of scientific-technical fields. Given these strengths and the ability to learn from one another, the U.S. National Academy of Sciences together with the National Institute for Advanced Studies in Bangalore, India, held a joint Indian-U.S. workshop to identify and examine potential areas for substantive scientific and technical cooperation that can support counterterrorism efforts through the Homeland Security Dialogue and through direct cooperation. India-United States Cooperation on Science and Technology for Countering Terrorism is the summary of that workshop. This report examines topics such as biological threats; protection of nuclear facilities; security (physical and cyber) for chemicals, chemical facilities and other critical infrastructure; and monitoring, surveillance, and emergency response. The report also identifies and examines promising areas for further Indian-U.S. cooperation.
Keywords: Conflict and Security Issues

Report of the Treasurer to the Council for the Year Ended December 31, 2003 - National Academy of Sciences (The National Academies Press, 2004)

Variation and Evolution in Plants and Microorganisms: Toward a New Synthesis 50 Years After Stebbins - National Academy of Sciences (The National Academies Press, 2000)
"The present book is intended as a progress report on [the] synthetic approach to evolution as it applies to the plant kingdom." With this simple statement, G. Ledyard Stebbins formulated the objectives of Variation and Evolution in Plants, published in 1950, setting forth for plants what became known as the "synthetic theory of evolution" or "the modern synthesis." The pervading conceit of the book was the molding of Darwin's evolution by natural selection within the framework of rapidly advancing genetic knowledge. At the time, Variation and Evolution in Plants significantly extended the scope of the science of plants. Plants, with their unique genetic, physiological, and evolutionary features, had all but been left completely out of the synthesis until that point. Fifty years later, the National Academy of Sciences convened a colloquium to update the advances made by Stebbins. This collection of 17 papers marks the 50th anniversary of the publication of Stebbins' classic. Organized into five sections, the book covers: early evolution and the origin of cells, virus and bacterial models, protoctist models, population variation, and trends and patterns in plant evolution.
Keywords: Biology and Life Sciences

Report of the Treasurer for the Year Ended December 31, 2011 - National Academy of Sciences (The National Academies Press, 2012)
The income that supports the activities of the National Academy of Sciences (NAS) comes from two major sources: program revenue received from sponsors to pay for the myriad studies and other activities undertaken each year by the National Research Council (NRC), and a much smaller sum that is obtained from our endowment under the endowment spending policies adopted by the Council. The goal of the endowment is to provide stable support for the Academy's programs and activities. To achieve this goal, the Council, acting on the recommendations of the Finance Committee, has historically authorized spending from the portfolio at a rate designed to maintain the purchasing power of the endowment over time. This Report of the Treasure of the National Academy of Sciences presents the financial position and results of operations as well as a review of the endowment, trust, and other long-term investments portfolio activities of our Academy for the year ended December 31, 2011. While this book provides essential financial summary to key personnel, it also serves as a vital informative resource for various members of the public, private, and governmental sectors.
Keywords: Policy for Science and Technology

In the Light of Evolution: Volume V: Cooperation and Conflict - National Academy of Sciences (The National Academies Press, 2011)
Biodiversity--the genetic variety of life--is an exuberant product of the evolutionary past, a vast human-supportive resource (aesthetic, intellectual, and material) of the present, and a rich legacy to cherish and preserve for the future. Two urgent challenges, and opportunities, for 21st-century science are to gain deeper insights into the evolutionary processes that foster biotic diversity, and to translate that understanding into workable solutions for the regional and global crises that biodiversity currently faces. A grasp of evolutionary principles and processes is important in other societal arenas as well, such as education, medicine, sociology, and other applied fields including agriculture, pharmacology, and biotechnology. The ramifications of evolutionary thought also extend into learned realms traditionally reserved for philosophy and religion. The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia--in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences--and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium "Cooperation and Conflict," which was sponsored by the National Academy of Sciences on January 7-8, 2011, at the Academy's Arnold and Mabel Beckman Center in Irvine, California. It is the fifth in a series of colloquia under the general title "In the Light of Evolution." The current volume explores recent developments in the study of cooperation and conflict, ranging from the level of the gene to societies and symbioses. Humans can be vicious, but paradoxically we are also among nature's great cooperators. Even our great conflicts-wars-are extremely cooperative endeavors on each side. Some of this cooperation is best understood culturally, but we are also products of evolution, with bodies, brains, and behaviors molded by natural selection. How cooperation evolves has been one of the big questions in evolutionary biology, and how it pays or does not pay is a great intellectual puzzle. The puzzle of cooperation was the dominant theme of research in the early years of Darwin's research, whereas recent work has emphasized its importance and ubiquity. Far from being a rare trait shown by social insects and a few others, cooperation is both widespread taxonomically and essential to life. The depth of research on cooperation and conflict has increased greatly, most notably in the direction of small organisms. Although most of In the Light of Evolution V: Cooperation and Conflict is about the new topics that are being treated as part of social evolution, such as genes, microbes, and medicine, the old fundamental subjects still matter and remain the object of vigorous research. The first four chapters revisit some of these standard arenas, including social insects, cooperatively breeding birds, mutualisms, and how to model social evolution.
Keywords: Biology and Life Sciences

China Bound, Revised: A Guide to Academic Life and Work in the PRC - National Academy of Sciences (The National Academies Press, 1994)
Being prepared in China, says one researcher, can mean "the difference between a headache and a productive day." Acclaimed by readers, this friendly and practical volume—now updated with important new information—offers all the details academic visitors need to make long-term stays in China productive, comfortable, and fun. Academic opportunities have been revived in the years since the Tiananmen Square event, and the book opens with an overview of what we have learned from our academic exchanges with China, the opportunities now available, and resources for more information. To help visitors prepare for daily life, the book covers everything from how to obtain the correct travel documents to what kinds of snack foods are available in China, from securing accommodations to having the proper gift for your Chinese dinner host. Frank discussions on the research and academic environments in China will help students, investigators, and teachers from their initial assignment to a danwei, or work unit, to leaving the country with research materials intact. The book offers practical guidelines on working with Chinese academic institutions and research assistants, arranging work-related travel, managing working relationships, resolving language issues, and—perhaps most important—understanding Chinese attitudes and customs toward study, research, and work life. New material in this edition includes an expanded section on science and social science field work, with a discussion of computers: which ones work best in China, how to arrange to bring your computer in, where to find parts and supplies, how to obtain repairs, and more. Living costs, health issues, and addresses and fax numbers for important services are updated. Guidance is offered on currency, transportation, communications, bringing children into China, and other issues. Based on the first-hand reports of hundreds of academic visitors to China and original research by the authors, this book will be useful to anyone planning to live and work in China: students, researchers, and teachers and their visiting family members, as well as business professionals.
Keywords: Education

A Positron Named Priscilla: Scientific Discovery at the Frontier - National Academy of Sciences (The National Academies Press, 1994)
A Positron Named Priscilla is a book of wonder, offering a fascinating, readable overview of cutting-edge investigations by many of today's leading young scientists. Written for anyone who loves science, this volume reports on some of the most exciting recent discoveries and advances in fields from astronomy to molecular biology. This new book is from one of the world's most prestigious scientific institutions, the National Academy of Sciences. The Academy provides an annual forum for the brightest young investigators to exchange ideas across disciplines—an exchange that was the spark for A Positron Named Priscilla. Each chapter is authored by a popular science writer who offers helpful historical perspectives, clear and well-illustrated explanations of current scientific thinking, and previews of future developments. The scope of topics and breadth of discussion ensure interest at all levels. Topics include: Planetary science and the compelling glimpse through the clouded atmosphere of Venus afforded by the spacecraft Magellan. Astrophysics and the emergence of helioseismology, a new field that allows researchers to probe the interior workings of the sun. Biology and what we have learned about DNA in the 40 years since its discovery; our current understanding of protein molecules, the "building blocks" of living systems; and the high-tech search for answers to the AIDS epidemic. Physics and our new-found ability to move and manipulate individual atoms on a surface. The book also tells the remarkable story of "buckyballs," or buckminsterfullerenes, a form of carbon discovered only a few years ago, that have the potential to be used in a variety of important applications, from superconductivity to nanotechnology. Mathematics and the rise of "wavelet" theory, and how mathematicians are applying it in sometimes startling ways, from assisting the FBI with fingerprint storage to coaxing the secrets from a battered recording of Brahms playing the piano. Geosciences and the search for "clocks in the earth" to make life-saving earthquake predictions. A Positron Named Priscilla is a "must" read for anyone who wants to keep up with a broad range of scientific endeavor.
Keywords: Explore Science; Math, Chemistry, and Physics

In the Light of Evolution: Volume III: Two Centuries of Darwin - National Academy of Sciences (The National Academies Press, 2009)
Two Centuries of Darwin is the outgrowth of an Arthur M. Sackler Colloquium, sponsored by the National Academy of Sciences on January 16-17, 2009. In the chapters of this book, leading evolutionary biologists and science historians reflect on and commemorate the Darwinian Revolution. They canvass modern research approaches and current scientific thought on each of the three main categories of selection (natural, artificial, and sexual) that Darwin addressed during his career. Although Darwin's legacy is associated primarily with the illumination of natural selection in The Origin, he also contemplated and wrote extensively about what we now term artificial selection and sexual selection. In a concluding section of this book, several science historians comment on Darwin's seminal contributions. Two Centuries of Darwin is the third book of the In the Light of Evolution series. Each installment in the series explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. The ILE series aims to interpret phenomena in various areas of biology through the lens of evolution and address some of the most intellectually engaging, as well as pragmatically important societal issues of our times.
Keywords: Biology and Life Sciences; Explore Science

(NAS Colloquium) Science, Technology and the Economy (The National Academies Press, 1996)
Keywords: Industry and Labor

The Positive Sum Strategy: Harnessing Technology for Economic Growth - Ralph Landau; Nathan Rosenberg (The National Academies Press, 1986)
This volume provides a state-of-the-art review of the relationship between technology and economic growth. Many of the 42 chapters discuss the political and corporate decisions for what one author calls a "Competitiveness Policy." As contributor John A. Young states, "Technology is our strongest advantage in world competition. Yet we do not capitalize on our preeminent position, and other countries are rapidly closing the gap." This lively volume provides many fresh insights including "two unusually balanced and illuminating discussions of Japan," Science noted.
Keywords: Industry and Labor

One Earth, One Future: Our Changing Global Environment - National Academy of Sciences (The National Academies Press, 1990)
Written for nonscientists, One Earth, One Future can help individuals understand the basic science behind changes in the global environment and the resulting policy implications that the population of the entire planet must face. The volume describes the earth as a unified system—exploring the interactions between the atmosphere, land, and water and the snowballing impact that human activity is having on the system—and presents perspectives on policies and programs that can both develop and protect our natural resources. One Earth, One Future discusses why such seemingly diverse issues as historical climate change, species diversity, and sea-level rise are part of a single picture—and how human activity is the critical element in that picture. The book concludes with practical examinations of economic, security, and development questions, with a view toward achieving improvements in quality of life without further environmental degradation. One Earth, One Future is must reading for anyone interested in the interrelationship of environmental matters and public policy issues.
Keywords: Earth Sciences; Environment and Environmental Studies

Chemical Ecology: The Chemistry of Biotic Interaction - Thomas Eisner; Jerrold Meinwald (The National Academies Press, 1995)
Chemical signals among organisms form "a vast communicative interplay, fundamental to the fabric of life," in the words of one expert. Chemical ecology is the the discipline that seeks to understand these interactions-to use biology in the search for new substances of potential benefit to humankind. This book highlights selected research areas of medicinal and agricultural importance. Leading experts review the chemistry of: Insect defense and its applications to pest control. Phyletic dominance—the survival success of insects. Social regulation, with ant societies as a model of multicomponent signaling systems. Eavesdropping, alarm, and deceit—the array of strategies used by insects to find and lure prey. Reproduction—from the gamete attraction to courtship nd sexual selection. The chemistry of intracellular immunosuppression. Topics also include the appropriation of dietary factors for defense and communication; the use of chemical signals in the marine environment; the role of the olfactory system in chemical analysis; and the interaction of polydnaviruses, endoparasites, and the immune system of the host.
Keywords: Math, Chemistry, and Physics; Biology and Life Sciences